2014
DOI: 10.1016/j.jcmg.2013.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Echocardiography in Asymptomatic HCM

Abstract: In asymptomatic or minimally symptomatic HCM patients, exercise stress testing provides excellent risk stratification, with a low event rate in patients achieving >100% of predicted METs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…A history of diabetes was the second strongest predictor of compromised exercise capacity in HOCM patients. The prevalence of diabetes in the present study (~9%) was in line with previous studies of HCM patients (3–16%) [ 9 , 10 , 11 , 16 , 28 ]. In support of the relationship between diabetes and reduced exercise capacity in HOCM, diabetes is independently associated with cardiac hypertrophy (often termed “diabetic cardiomyopathy”), compromised systolic and diastolic function, and risk of heart failure [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A history of diabetes was the second strongest predictor of compromised exercise capacity in HOCM patients. The prevalence of diabetes in the present study (~9%) was in line with previous studies of HCM patients (3–16%) [ 9 , 10 , 11 , 16 , 28 ]. In support of the relationship between diabetes and reduced exercise capacity in HOCM, diabetes is independently associated with cardiac hypertrophy (often termed “diabetic cardiomyopathy”), compromised systolic and diastolic function, and risk of heart failure [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, obstruction is associated with a further reduction in VO 2 peak in HCM [ 9 , 10 , 14 , 15 ]. HCM patients also exhibit numerous cardiovascular risk factors, including diabetes, arterial hypertension, and coronary artery disease [ 9 , 10 , 11 , 16 , 17 ]. However, the contribution of these cardiovascular risk factors to the worsening of VO 2 peak in patients with HOCM is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…6, 7, 14 Likewise a new study from Desai et al found exercise capacity to be a predictor of SCD in HCM patients. 23 All these parameters are also relevant in high gradient HCM and in our cohort of obstructive HCM the exercise testing provided information useful in risk stratification in a substantial amount of patients.…”
Section: Discussionmentioning
confidence: 85%
“…25,26 Stress testing can also be useful for risk stratifi cation in asymptomatic patients, with one study showing that those who achieve more than 100% of their age-and sex-predicted metabolic equivalents have a low event rate. 27…”
Section: Stress Testing For Risk Stratifi Cationmentioning
confidence: 99%